2019
DOI: 10.3389/fphar.2018.01448
|View full text |Cite
|
Sign up to set email alerts
|

Systems Pharmacology Dissection of Multi-Scale Mechanisms of Action of Huo-Xiang-Zheng-Qi Formula for the Treatment of Gastrointestinal Diseases

Abstract: Multi-components Traditional Chinese Medicine (TCM) treats various complex diseases (multi-etiologies and multi-symptoms) via herbs interactions to exert curative efficacy with less adverse effects. However, the ancient Chinese compatibility theory of herbs formula still remains ambiguous. Presently, this combination principle is dissected through a systems pharmacology study on the mechanism of action of a representative TCM formula, Huo-xiang-zheng-qi (HXZQ) prescription, on the treatment of functional dyspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 105 publications
0
35
0
Order By: Relevance
“…This flowchart really solves the molecular mechanism of some formulas of TCM in treating complex diseases. Such as: Hua Yu Qiang Shen Tong Bi formula treats rheumatoid arthritis ( Wang et al., 2019 ), Shen Qi Wan treats kidney yang deficiency syndrome ( Zhang et al., 2019 ), and Huo Xiang Zheng Qi formula treats functional dyspepsia ( Zhao et al., 2018 ). However, there still exists some problems, such as false positive and noise in the predicted targets of components.…”
Section: Discussionmentioning
confidence: 99%
“…This flowchart really solves the molecular mechanism of some formulas of TCM in treating complex diseases. Such as: Hua Yu Qiang Shen Tong Bi formula treats rheumatoid arthritis ( Wang et al., 2019 ), Shen Qi Wan treats kidney yang deficiency syndrome ( Zhang et al., 2019 ), and Huo Xiang Zheng Qi formula treats functional dyspepsia ( Zhao et al., 2018 ). However, there still exists some problems, such as false positive and noise in the predicted targets of components.…”
Section: Discussionmentioning
confidence: 99%
“…And the results showed that HD-SB displayed much more potent inhibitory effects on tumor growth compared with HD or SB. In recent years, network pharmacology analysis was successfully used to predict the underlying function mechanisms of TCM formulas for cancer, depression, and cardiovascular disease treatment (Zhao et al, 2019). Network pharmacology is a systems biology-based methodology for evaluating pharmacokinetics (ADME properties of drugs) and target prediction, as well as investigating the multipharmacological effects of traditional medicines at the molecular level (Di et al, 2018;Gong et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Through the overall analysis of the "drug-target-gene-disease" of the biological system, the interaction mechanism between the drug and the body is clarified. The systematic and holistic view of this research method is very similar to TCM theory, and network pharmacology has achieved some results in explaining the mechanism of action of TCM [10,11].…”
Section: Introductionmentioning
confidence: 90%